2021
DOI: 10.1093/trstmh/trab041
|View full text |Cite
|
Sign up to set email alerts
|

Liver stiffness is able to differentiate hepatosplenic Schistosomiasis mansoni from liver cirrhosis and spleen stiffness may be a predictor of variceal bleeding in hepatosplenic schistosomiasis

Abstract: Background Ultrasonography is limited for differentiating portal hypertension due to liver cirrhosis from that secondary to hepatosplenic schistosomiasis (HSS). We aimed to investigate the role of transient elastography (TE) in differentiating HSS mansoni from cirrhosis and the factors associated with liver and spleen stiffness (LS and SS) in HSS. Method A cross-sectional study was conducted including patients with HSS manson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In fact, recent studies have shown that the measurement of spleen stiffness by TE and pSWE correlates with that of liver stiffness and of portal hypertension in patients with HSS[ 20 , 52 ]. Accordingly, spleen stiffness may also be a predictor of variceal bleeding in HSS and may be further investigated for predicting HSS complications[ 57 ].…”
Section: Noninvasive Markers Of Ppfmentioning
confidence: 99%
“…In fact, recent studies have shown that the measurement of spleen stiffness by TE and pSWE correlates with that of liver stiffness and of portal hypertension in patients with HSS[ 20 , 52 ]. Accordingly, spleen stiffness may also be a predictor of variceal bleeding in HSS and may be further investigated for predicting HSS complications[ 57 ].…”
Section: Noninvasive Markers Of Ppfmentioning
confidence: 99%
“…Transient elastography-FibroScan quantitatively evaluates liver fibrosis by measuring LSM using a shear wave technique[ 88 ]. Its non-invasive diagnostic efficacy for liver fibrosis has been verified in a variety of causes of chronic liver disease[ 85 , 89 ].…”
Section: Value Of Liver Stiffness Measurement During Early Hsct-sos D...mentioning
confidence: 99%